Coachee Satisfaction and Beyond : A Systematic Review of the Coaching Relationship - Yi-Lang Lai; Almuth McDowall (Coaching Psykologi: The Danish Journal of Coaching Psychology, 2016)
This report summarises a conference paper presented at the 4th International Congress hosted by the British Psychological Society’s Special Group in Coaching Psychology in London, December 2014. A further discussion of a Systematic Review (SR) study which aimed to strengthen evidence-based coaching through reviewing existing studies in Coaching Psychology was presented. This SR focused on investigating effective coaching psychologists’ attributes for a productive coaching relationship and how to facilitate desired outcomes. The coaching relationship has been established as a key indicator for a positive coaching outcome through several primary studies. Nevertheless existing competency frameworks of main governing associations (e.g. the British Psychological Society) have not yet outlined explicit behavioural indicators for facilitating an effective coaching relationship. Hence, it is an essential step to study common factors for an effective coaching process and to what extent coaches’ attributes impact the coach-coachee relationship. The details of this SR study has been published in International Coaching Psychology Review in 2014 (Lai & Almuth, 2014); this short paper will discuss how this SR study results expand commonly used coaching evaluation from coachees’ satisfaction to comprise more concrete outcome measurement.